Influence of ejection temperature on structure and glass transition behavior for Zr-based rapidly quenched disordered alloys. (1st September 2016) - Wang, X.H.; Inoue, A.; Kong, F.L.; Zhu, S.L.; Stoica, M.; Kaban, I.; Chang, C.T.; Shalaan, E.; Al-Marzouki, F.; Eckert, J.
Abstract: We examined the influence of ejection liquid temperature ( T el ) on the structure, thermal stability and crystallization of ZrAlNiCu ribbons prepared by the melt-spinning technique. The increase in T el was found to cause the formation of an oxide phase on the ribbon surface, more loose atomic configurations, the absence of glass transition (GT) and supercooled liquid (SL) region, and the rise of crystallization temperature. The changes in the GT and SL region occur reversibly by controlling the T el . Neither the change in alloy composition except oxygen nor the difference in crystallized phases is seen. Their hardness increases significantly by the disappearance of GT and SL region. The reversible changes in the appearance and disappearance of GT and SL region was found for different Zr-based glassy ribbons, being independent of alloy compositions. The disappearance is presumably due to the change in atomic configurations from high-coordinated to less-coordinated atomic packing in the melt-spun ribbons by freezing high-temperature liquid. The observed phenomenon of the reversible changes provides a novel opportunity for deep understanding of mutual correlations among liquid structure, GT, stability of SL and bulk glass-forming ability for metallic alloys. Graphical abstract: